The climate of history in a planetary age - Chakrabarty, Dipesh; Latour, Bruno (Chicago ; London : The University of Chicago Press, 2021)
"For the past decade, no thinker has had a greater influence on debates about the meaning of climate change in the humanities than the historian Dipesh Chakrabarty. Climate change, he has argued, upends our ideas about history, modernity, and globalization, and confronts humanists with the kinds of universals that they have been long loath to consider. Here Chakrabarty elaborates this thesis for the first time in book form and extends it in important ways. "The human condition," Chakrabarty writes, "has changed." The burden of "The Climate of History in a Planetary Age" is to grapple with what this means for historical and political thought. Chakrabarty argues that our times require us to see ourselves from two perspectives at once: the planetary and the global. The global (and thus globalization) are human constructs, but the planetary Earth system de-centers the human. Chakrabarty explores the question of modern freedoms in light of this globe/planet distinction. He also considers why Marxist, postcolonial, and other progressive scholarship has failed to account for the problems of human history that anthropogenic climate change poses. The book concludes with a conversation between Chakrabarty and the French anthropologist Bruno Latour. Few works are as likely to shape our understanding of the human condition as we open ourselves to the implications of the Anthropocene"--
Introduction : intimations of the planetary -- The globe and the planet. Four theses; Conjoined histories; The planet : a humanist category -- The difficulty of being modern. The difficulty of being modern; Planetary aspirations : reading a suicide in India; In the ruins of an enduring fable -- Facing the planetary. Anthropocene time -- Toward an anthropological clearing -- Postscript : the global reveals the planetary : a conversation with Bruno Latour.
Includes bibliographical references and index.
BIGD
Amazon.com
Keywords: Climatic changes -- Social aspects; Climatic changes -- Political aspects; Globalization; Human ecology; Civilization, Modern; History -- Philosophy